Ergo Design of Mentoring in the National Ecosystem of Vocational Education in The Period of the 10th Technological Order - Valery Vladimirovich Glushchenko (Universitas Pendidikan Indonesia (UPI), 2022)
The target of this study is to introduce ergo design for mentoring in the ecosystem of vocational education in the period of the 10th technological order. The purpose of the article is to improve the quality of vocational education in the conditions of the 10th technological order. To achieve these goals, the following tasks are solved. The evolution of vocational education technologies in the process of changing technological orders is investigated. The concept and essence of the ergo design of mentoring as an element of the national ecosystem of vocational education are clarified. Mentoring technologies in postgraduate additional vocational education in the conditions of the 10th technological order is investigated. Methodological provisions of mentoring in postgraduate additional vocational education in the conditions of the 10th technological order is developed.